Collective living and universal housing design concepts towards self-sufficient community / Harlina Mohamad Ali, Mazuiyah Mohd Dom and Muhamad Shamin Sahrum. - Mohamad Ali, Harlina; Mohd Dom, Mazuiyah; Sahrum, Muhamad Shamin (Universiti Teknologi MARA Cawangan Selangor, 2018)
The idea of self-sufficient community develops as the awareness of protecting the environment arises. Due to the differences in socio-cultural backgrounds, a community could become less cohesive. Thus, communal– based activities should be implemented in a community to inculcate community spirit and to promote collective living. To achieve this, housing schemes should be provided with collective spaces for deßned communal activities. Universal Housing Design principles can be implemented to the layout plans, where the needs of diverse people and abilities over time are addressed. The paper advocates collective living strategies and Universal Housing Design principles towards achieving a self-sufßcient community.